A scintillator-based range telescope for particle therapy - Kelleter, Laurent; Radogna, Raffaella; Volz, Lennart; Attree, Derek; Basharina-Freshville, Anastasia; Seco, Joao; Saakyan, Ruben; Jolly, Simon (Physics in medicine and biology, 2020)
The commissioning and operation of a particle therapy centre requires an extensive set of detectors for measuring various parameters of the treatment beam. Among the key devices are detectors for beam range quality assurance. In this work, a novel range telescope based on a plastic scintillator and read out by a large-scale CMOS sensor is presented. The detector is made of a stack of 49 plastic scintillator sheets with a thickness of 2-3 mm and an active area of 100 × 100 mm2, resulting in a total physical stack thickness of 124.2 mm. This compact design avoids optical artefacts that are common in other scintillation detectors. The range of a proton beam is reconstructed using a novel Bragg curve model that incorporates scintillator quenching effects. Measurements to characterise the performance of the detector were carried out at the Heidelberger Ionenstrahl-Therapiezentrum (HIT, Heidelberg, GER) and the Clatterbridge Cancer Centre (CCC, Bebington, UK). The maximum difference between the measured range and the reference range was found to be 0.41 mm at a proton beam range of 310 mm and was dominated by detector alignment uncertainties. With the new detector prototype, the water-equivalent thickness of PMMA degrader blocks has been reconstructed within ± 0.1 mm. An evaluation of the radiation hardness proves that the range reconstruction algorithm is robust following the deposition of 6,300 Gy peak dose into the detector. Furthermore, small variations in the beam spot size and transverse beam position are shown to have a negligible effect on the range reconstruction accuracy. The potential for range measurements of ion beams is also investigated.
Gesehen am 25.09.2020